ANALISIS PENGARUH DEWAN KOMISARIS INDEPENDEN, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, TOTAL ASSET TURN OVER, DAN LEVERAGE TERHADAP FINANCIAL DISTRESS - Andri Aji Saputra; Wisnu Mawardi (Diponegoro Journal of Management, 2022)
This study aims to examine the effect of independent commissioners, managerial ownership, institutional ownership, total asset turnover, and leverage on financial distress. The example used is the property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2017-2020 period which is selected using the purposive sampling method. The number of samples obtained is 16 with 4 years of observation so a sample of 64 is obtained. The analysis used is logistic regression analysis with the IBM SPSS 25 program after having previously carried out the goodness of fit to test the feasibility of the data. The results of this study indicate that total asset turnover has a significant negative effect on financial distress. Independent board of commissioners, managerial ownership, institutional ownership, and leverage do not affect financial distress. In this test, the results of the Nagelkerke R Square test were found to be 52.2% and the value for Hosmer and Lemeshow Goodness of Fit was 96.4%.